Cytotoxicity, cellular uptake, and DNA interactions of new monodentate ruthenium(II) complexes containing terphenyl arenes - Bugarcic, Tijana; Nováková, Olga; Halámiková, Anna; Marková, Lenka; Vrána, Oldřich; Kašpárková, Jana; Habtemariam, Abraha; Parsons, Simon; Sadler, Peter J; Brabec, Viktor (Journal of medicinal chemistry, 2008)
We have compared the cancer cell cytotoxicity, cell uptake, and DNA binding properties of the isomeric terphenyl complexes [(eta(6)-arene)Ru(en)Cl](+), where the arene is ortho- (2), meta- (3), or para-terphenyl (1) (o-, m-, or p-terp). Complex 1, the X-ray crystal structure of which confirms that it has the classical "piano-stool" geometry, has a similar potency to cisplatin but is not cross-resistant and has a much higher activity than 2 or 3. The extent of Ru uptake into A2780 or A2780cis cells does not correlate with potency. Complex 1 binds to DNA rapidly and quantitatively, preferentially to guanine residues, and causes significant DNA unwinding. Circular and linear dichroism, competitive binding experiments with ethidium bromide, DNA melting, and surface-enhanced Raman spectroscopic data are consistent with combined intercalative and monofunctional (coordination) binding mode of complex 1. This unusual DNA binding mode may therefore make a major contribution to the high potency of complex 1.
Keywords: Spectrum Analysis; spektrální analýza; Neoplasms; superhelikální DNA; Ruthenium; nádorové buněčné linie; Cell Line, Tumor; lidé; Guanine; Humans; ruthenium; Nucleic Acid Denaturation; guanin; Binding Sites; Structure-Activity Relationship; Animals; denaturace nukleových kyselin; DNA, Superhelical; Crystallography, X-Ray; protinádorové látky; Antineoplastic Agents; zvířata; Terphenyl Compounds; DNA; nádory; terfenylové sloučeniny; vazebná místa; organokovové sloučeniny; vztahy mezi strukturou a aktivitou; Organometallic Compounds; krystalografie rentgenová